Effectiveness of traditional and sling exercise strength training in novice women - Dannelly, B. D.; Otey, S. C.; Croy, T.; Harrison, B.; Rynders, C.; Hertel, J.; Weltman, A. (The Journal of Strength and Conditioning Research, 2011)
Strength training programs often combine closed (CKCE) and open (OKCE) kinetic chain exercises. Several studies report that CKCE may be more effective than OKCE in improving performance related measures in lower body training. Our lab recently found upper-body CKCE was as effective as OKCE training for strength gains and that CKCE was more effective than OKCE for improving throwing performance. To our knowledge the effectiveness of a strength-training program that uses exclusively CKCE is unknown. PURPOSE: The present study compared the effectiveness of a CKCE training program and OKCE training program on several strength and balance measures in novice female strength trainers. Novice females were chosen as they are oftentimes intimidated by a traditional weight training setting. METHODS: Eighteen participants were randomized to one of two training interventions: OKCE with traditional exercises, and CKCE with sling-based exercises. Participants completed six sets of strength training exercises per week for 13 weeks. Pre- and post-training evaluation included: 1 RM leg and bench press; maximum sling exercise pushups; isokinetic concentric phase peak torque and peak power for knee flexion and extension and for shoulder internal and external rotation; lateral step-down test; and the anterior, posteromedial, and posterolateral components of the Star Excursion Balance Test. RESULTS: The OKCE group (bench press pre x = 67.5 ± 11.7, bench press post x = 80.6 ± 18.8, leg press pre x = 111.7 ± 62.8, leg press post x = 190.0 ± 71.2 lb) and CKCE group (bench press pre x = 74.4 ± 16.8, bench press post x = 83.8 ± 13.3, leg press pre x = 187.5 ± 74.0, leg press post x = 238.8 ± 96.3 lb) improved 1RM leg press (p<0.0001) and 1RM bench press (p = 0.0001). There was a significant group × time interaction (p<0.001) for sling exercise push-ups (OKCE pre = 5.8 ± 10.2, OKCE post = 5.5 ± 8.9, CKCE pre = 7.6 ± 6.9, CKCE post = 19.3 ± 6.4). For all isokinetic measures, including peak torque (PT) and peak power (PP), significant increases were observed pre to post training for knee extension, knee flexion, shoulder internal rotation, and shoulder external rotation (improvements ranged from 4.5 to 26%), with no differences observed in improvement between groups. Both OKCE and CKCE strength training elicited similar changes in balance with the exception of the posterolateral direction measure, where CKCE training significantly improved balance and OKCE resulted in a slight decline in balance. CONCLUSIONS: CKCE training is equally as effective as OKCE training in eliciting improvements during the initial phases of a strength-training program in novice women. The fact that only CKCE improved sling exercise push ups supports previous findings suggesting functional superiority of CKCE. PRACTICAL APPLICATIONS: Novice female strength trainers are often hesitant to begin an OKCE program due to intimidation and fear of a weight room. These women may be more inclined to undertake a CKCE training program that can be conducted outside of a weight room and can substitute CKCE for OKCE without a detrimental effect on strength. Although only novice females were examined, data from the present study as well data from previous studies indicate substituting sling based CKCE for traditional OKCE is effective for both strength gains and functional improvement..